2022
DOI: 10.1073/pnas.2203783119
|View full text |Cite
|
Sign up to set email alerts
|

ASPM promotes ATR-CHK1 activation and stabilizes stalled replication forks in response to replication stress

Abstract: ASPM is a protein encoded by primary microcephaly 5 ( MCPH5 ) and is responsible for ensuring spindle position during mitosis and the symmetrical division of neural stem cells. We recently reported that ASPM promotes homologous recombination (HR) repair of DNA double strand breaks. However, its potential role in DNA replication and replication stress response remains elusive. Interestingly, we found that ASPM is dispensable for DNA replication under unperturbed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…ssDNA/dsDNA pulldown assays were performed as previously described [26] . In brief, biotinylated DNA oligomers (sense strand: 5′-AACCTGTCGTGCCAGCTGCA-biotin-3′; anti-sense strand: 5′-TGCAGCTGGCACGACAGGTTTTAATGAATCGGCCAACGCGCGGGGAGAGGCGGTTTGCGTATTGGGCGCTCTTCCGCTTCGCAG CGAGTC-3′) were annealed to generate ssDNA/dsDNA.…”
Section: Methodsmentioning
confidence: 99%
“…ssDNA/dsDNA pulldown assays were performed as previously described [26] . In brief, biotinylated DNA oligomers (sense strand: 5′-AACCTGTCGTGCCAGCTGCA-biotin-3′; anti-sense strand: 5′-TGCAGCTGGCACGACAGGTTTTAATGAATCGGCCAACGCGCGGGGAGAGGCGGTTTGCGTATTGGGCGCTCTTCCGCTTCGCAG CGAGTC-3′) were annealed to generate ssDNA/dsDNA.…”
Section: Methodsmentioning
confidence: 99%
“…Affinity purification experiments showed that FLAG-GFP-ASPM interacts with several proteins involved in DNA replication, including the five subunits of the replication factor complex (RFC1-5), the BRCA2 factor involved in both DSB repair and protection of the replication forks, the MCM5 core subunit of the MCM complex that promotes double-strand DNA unwinding at the replication origins, the TopBP1 topoisomerase, and the RAD9 and RAD17 factors that together with TopBP1 associate to the replication forks, facilitating activation of the ATR-CHK1 kinases [ 80 ]. Despite its multiple interactions with the DNA replication machinery, ASPM is dispensable for DNA replication under unperturbed conditions [ 80 ]. However, after replication stress by either hydroxyurea or aphidicolin, ASPM shields the nascent DNA strand from MR11-mediated degradation at the stalled replication forks, thus preventing genomic instability [ 80 ].…”
Section: Asp/aspm Functions In Interphase Nucleimentioning
confidence: 99%
“…Despite its multiple interactions with the DNA replication machinery, ASPM is dispensable for DNA replication under unperturbed conditions [ 80 ]. However, after replication stress by either hydroxyurea or aphidicolin, ASPM shields the nascent DNA strand from MR11-mediated degradation at the stalled replication forks, thus preventing genomic instability [ 80 ].…”
Section: Asp/aspm Functions In Interphase Nucleimentioning
confidence: 99%
“…Specifically, it has recently been found that ASPM can be recruited to DNA damage sites and is required for efficient homologous recombination repair ( Xu et al, 2021 ). Moreover, ASPM is involved in stabilization of stalled fork in response to replication stress ( Wu et al, 2022 ). Accordingly, ASPM disruption leads to increased DNA damage in cerebellar progenitor cells ( Williams et al, 2015 ).…”
Section: Mechanisms Of Tp53 Activation In Mcph: Dna Damage and Beyondmentioning
confidence: 99%